Cooperativismo, agricultura familiar e a adequação das propriedades rurais ao modelo de produção agroindustrial em Palotina - PR - Vendrame, André Luís (2014)
The main goal of this research was to analyze the needs, the capacity of adaptation and the current conditions and aspirations of the members from the cooperative C.vale, from Palotina, Paraná, related to its productive unities inclusion in the new role of production, agro industrial, competitive and globalized, as a cooperative method. This study has the hypothesis that the farmers with a higher capacity of investment, with higher unities of production, with a diverse production and with a higher associative cultivar, have a higher adaptable capacity and insertion in the new role of agro industrial production, in which the smaller farms are subordinate to this. In order to achieve the main goals of this study, it was used a literary review related to the theme as a construction of its theory part and a field research as a local study to the characterization and analyze of productive unities and its behavior related to this research. The interviews were done with cooperates from cooperative C.vale who live in Palotina-Pr. The members were selected as an aleatory way, in which were taken the registers of rural producers in Prefeitura Municipal de Palotina. This study reveals that the labor in a small property is related in a high part to the sectors which are not related to the productive unity, in which the pluriativity in the familiar agriculture is represented as an important element to the reproduction of its category. The current rural sector is the scenery of evasion of the young people, mainly from those who show a high educational level, being this evasion a result of the low payment given for the small properties nowadays, being evident the lack of resources in an investment in the diversity of the activities or in the increasing of the activities that are done in the place. The study pointed that there is a large number of concentration in integrated poultry activity, in proprieties with more than 30 bushels, what indicates the existence of obstacles in the insertion of a small propriety in this productive branch. Lastly, it was evidenced the difficult that the families farmer from Palotina, as its union and cooperative representatives, have in order to seek another way of restructuration of the productive unity, which aims to gain the higher market with new concepts of production.